Amanita vladimirii (Amanitaceae, Agaricales), a new European species in section Vaginatae - Ševčíková, Hana; Hanss, Jean-Michel; Moreau, Pierre-Arthur (Phytotaxa, 2021)
Amanita vladimirii, a new species in sect. Vaginatae, is described and illustrated based on collections from the Czech Republic and France. The distinctive sequences of the LSU, ITS and tef1-α genetic markers, support the status of A. vladimirii as a new species. Amanita vladimirii is characterised by a greyish pileus striate at margin, a whitish stipe; and a relatively thin, but firm, membranous volva which is externally white with brownish yellow tinges where touched and internally is white-beige or greyish beige. Microscopically, the universal veil is composed of 3 layers; globose basidiospores; a ramose subhymenium; lamellar trama reduced to a mediostratum composed of parallel elements and a pileipellis without a differentiated subpellis.